The Application of IT-based Audio-Visual Learn Media in Improving Al-Istimā’ Skills among Students Darussalam Gontor Modern Islamic Boarding School Campus 11 Ittihadul Ummah Poso - Ahmad Faqih Ramadhan Rowa; Ubay Ubay; Jafar Sidik; Muammar Ahsanul Hilmar (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
The implementation of IT-based learning media has recently had a positive impact on the learning process of students, particularly in Arabic language lessons, so that IT-based learning media can now be found in almost all educational institutions, including Islamic boarding schools. This study examines the implementation of IT-based audio-visual learning media in enhancing Mahārah al-Istimā’ among students at PMDG Campus 11 Ittihadul Ummah Poso. With theacher from the Language Advisory Council (LAC) as the primary data source and PMDG students at Campus 11 Ittihadul Ummah Poso as the secondary data source, this study employs a qualitative descriptive field research methodology. Data collection was conducted through documentation, interviews, and observations. The results of the study indicate that the implementation of IT-based audio-visual learning media in improving Mahārah al-Istimā’ among PMDG students at Campus 11 Ittihadul Ummah Poso. The implementation was carried out during weekly activities every Friday morning, consisting of three stages: the introductory stage, the core stage, and the evaluation stage. Regarding the impact of the implementation of audio-visual media, the students were able to understand vocabulary, comprehend sentences, understand a text, and provide responses to the text.